2017
DOI: 10.1177/1747493017694395
|View full text |Cite
|
Sign up to set email alerts
|

An update of the Italian Stroke Organization–Stroke Prevention Awareness Diffusion Group guidelines on carotid endarterectomy and stenting: A personalized medicine approach

Abstract: Although proof-based medicine has generated much valid evidence for the drawing up of guidelines and recommendations for best clinical practice in symptomatic and asymptomatic carotid stenosis, whether and when it is better to employ endarterectomy or stenting as the intervention of choice still remain matters of debate. Moreover, guidelines have been targeted up to now to the 'representative' patient, as resulting from the statistical analyses of the studies conducted on the safety and efficacy of both interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…As a starting point, we characterized lymphocyte populations in human atherosclerotic plaques obtained by endarterectomy, a surgical procedure to remove the atheromatous plaque from carotids (31). Donor's characteristics are presented in Table 1 (section Materials and Methods).…”
Section: Characterization Of Human Atherosclerotic Plaques: Tregs Accmentioning
confidence: 99%
“…As a starting point, we characterized lymphocyte populations in human atherosclerotic plaques obtained by endarterectomy, a surgical procedure to remove the atheromatous plaque from carotids (31). Donor's characteristics are presented in Table 1 (section Materials and Methods).…”
Section: Characterization Of Human Atherosclerotic Plaques: Tregs Accmentioning
confidence: 99%
“…52 It was suggested that the stroke risk of individual ACS patients should be stratified and the treatment should be tailored to each patient's needs. [53][54][55] Risk prediction tools/improvements in CEA outcomes for ACS patients Improvements in MRI/CT imaging techniques and technology nowadays make it possible to identify plaque features associated with increased stroke risk. 56,57 Irregular plaque morphology and/or ulcerated plaque surface are associated with an increased risk for future stroke.…”
Section: Patient Adherence With Bmtmentioning
confidence: 99%
“…All measurements were repeated thrice, and the mean values were calculated. Acute organ damage was diagnosed in accordance with international guidelines (16)(17)(18)(19).…”
Section: Selection Of Participantsmentioning
confidence: 99%